Morphological Diversity of “Tuni” and “Afo” Cloves, Endemic to the Maluku Islands, Indonesia - Lating, Muhammad Fajri; Mahulette, Asri Subkhan; Kilkoda, Abdul Karim Kilkoda (Journal of Tropical Crop Science, 2024)
“Tuni” and “Afo” cloves are endemic clove varieties from the Maluku islands. Until now, there is still little information on morphological diversity in plant populations and information on the characteristics between the two varieties. The research aims to provide information on the morphological diversity and characteristics of “Tuni” and “Afo” cloves from the Maluku Islands. Morphological characterization of the “Tuni” variety of cloves was carried out at its distribution location on Ambon Island, Maluku Province. In contrast, “Afo” cloves were characterized at their distribution location on Ternate Island, North Maluku Province. The research was carried out in July 2023-May 2024. The used for morphological identification was the modified Tropical Fruit Descriptors. The characterized clove plants consisted of 30 “Tuni” clove plants and 30 “Afo” clove plants, so a total of 60 plants were characterized. The results of the Hierarchical Cluster Analysis (HCA) based on 54 morphological characters that were carried out showed two groups with a dissimilarity coefficient of 44%. The first group is a group of “Tuni” clove accessions, which are clustered with a similarity of 91%, and the second group is a group of “Afo” clove accessions, which are clustered with a similarity of 90%. The results of Principle Component Analysis (PCA) obtained a total diversity of 75.4%, where the specific characteristics of “Tuni” cloves obtained were stem bark color, crown shape, branching angle, leaf thickness, old leaf color, shoot color, leaf petiole tip color, flower stalk weight, flower length, flower tube diameter. The specific characteristics of “Afo” cloves obtained from PCA are plant height, stem circumference, North-South canopy width, East-West canopy width, leaf length, leaf texture, leaf spiciness, ripe picked flower color, picked ripe flower crown color, ripe fruit color, and color seed.